The Effect of The Drill Training Method on Increasing the Accuracy of Volleyball Services - Kharisma, Yudhi; Mubarok, Moch. Zakky; Hermawan, Bagus (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This study aimed to examine the method to improve the accuracy of the upper serve in volleyball games. The method applied is experimental with a pretest-posttest design. The research participants are 20 female active students of SMPN 1 Tukdana who attend volleyball extracurricular activities. The treatment provided is top-service training using the drill method with target aids. The instrument utilized was the volleyball skills test from Russell-Lange. This skills test measures the level of service mastery in volleyball. The research results obtained an average initial test of 14.75, a final test of 25, a standard deviation of the initial test of 3.08, and a final test of 4.59. Data analysis results of normality test L count < L table is 0.04. This number stated the normal result because its value is lower than the maximum passing grade (< 0.20). Due to the results of the calculations, t count < t table, specifically 1.73, is < 2.10, which means that Ho is accepted. The results reveal that applying the drill training method effectively improves the quality of the volleyball top serve.